2009
DOI: 10.1016/j.bpj.2009.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Common Crowding Agents Have Only a Small Effect on Protein-Protein Interactions

Abstract: Studies of protein-protein interactions, carried out in polymer solutions, are designed to mimic the crowded environment inside living cells. It was shown that crowding enhances oligomerization and polymerization of macromolecules. Conversely, we have shown that crowding has only a small effect on the rate of association of protein complexes. Here, we investigated the equilibrium effects of crowding on protein heterodimerization of TEM1-beta-lactamase with beta-lactamase inhibitor protein (BLIP) and barnase wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
159
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(172 citation statements)
references
References 48 publications
13
159
0
Order By: Relevance
“…Phillip et al (2009) found a negligible impact on the binding affinity of TEM1-β-lactamase with its inhibitor β-lactamase and barnase with barstar due to increased PEG 1000 crowding that varied up to 30 % packing fraction. Results from experimental studies (Crowley et al 2008;Phillip et al 2009) suggest the presence of an attractive interaction between PEG molecules and proteins. Based on our earlier discussion, attractive protein-crowder interactions will actually counteract the stabilizing effect of excluded volume on complex formation and can help explain this trend.…”
Section: Effects Of Crowding On the Thermodynamic Stability Of A Protmentioning
confidence: 89%
See 2 more Smart Citations
“…Phillip et al (2009) found a negligible impact on the binding affinity of TEM1-β-lactamase with its inhibitor β-lactamase and barnase with barstar due to increased PEG 1000 crowding that varied up to 30 % packing fraction. Results from experimental studies (Crowley et al 2008;Phillip et al 2009) suggest the presence of an attractive interaction between PEG molecules and proteins. Based on our earlier discussion, attractive protein-crowder interactions will actually counteract the stabilizing effect of excluded volume on complex formation and can help explain this trend.…”
Section: Effects Of Crowding On the Thermodynamic Stability Of A Protmentioning
confidence: 89%
“…Thus, to answer the above questions, many experimental studies have been performed using synthetic polymers or specific proteins as crowding agents. These studies have addressed both the thermodynamics and kinetics of protein-protein interactions in a crowded environment (Minton and Wilf 1981;Minton 1983;Jarvis and Ring 1990;van den Berg et al 1999;Wenner and Bloomfield 1999;Morar et al 2001;Patel et al 2002;Kozer and Schreiber 2004;Zorrilla et al 2004;Phillip et al 2009;Wang et al 2011;Fodeke and Minton 2011). Using "inert" crowding agents, the primary focus in most of these studies was to understand the excluded volume effects of crowding agents on the formation of protein complexes (Minton 1983;Kim et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 kDa), translational diffusion rates are estimated to be reduced by a factor of approximately 5 (17,31,32). Although competitive interactions and slower diffusion may act to reduce binding rates, the depletion force (or the caging effect) acts to enhance it (33)(34)(35). It seems that these factors operate in opposite directions, yielding only a minor modulation of binding rates compared to simple buffer solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Association rate constants were determined using a stopped-flow fluorescence spectrometer (Applied PhotoPhysics) under pseudo-first-order conditions (20). Dissociation rate constants for both TEM1-BLIP and CyTEM-YBLIP wild-type complexes were determined using the ProteOn XPR36 (BioRad) as described before (34). Dissociation rate constant of the TEM1 E104A -YBLIP WT complex was determined as described in Cell Extract Measurements.…”
Section: Cell Extractmentioning
confidence: 99%